EKONOMI LINGKUNGAN SEBAGAI PILAR PEMBANGUNAN BERKELANJUTAN DI INDONESIA: TANTANGAN, PELUANG, DAN PERAN GENERASI MUDA - Syahrul Arifin; Rosalina Kumalawati; Ellyn Normelani (KOLABORATIF: Jurnal Isu Sosial dan Tinjauan Kebijakan, 2023)
Environmental economics is a branch of science that seeks to bridge the conflict of interest between economic growth and environmental sustainability. In the context of Indonesia, issues of deforestation, land degradation, pollution, and exploitation of natural resources show that development is often carried out without considering ecological costs. This study aims to examine the role of environmental economics in promoting sustainable development, while also exploring the challenges and opportunities faced by Indonesia. The method used is a literature study, reviewing more than ten relevant journals and books related to the concepts of environmental economics, sustainable development, and their application in national policy. The results of the study show that although environmental economic theories—such as Pigou's internalization of externalities, Costanza's valuation of ecosystem services, and Geissdoerfer's circular economy concept—provide a strong foundation for environmentally-friendly development, their implementation in Indonesia still However, there are significant opportunities through institutional strengthening, the application of green economic instruments, and the participation of the younger generation in environmentally friendly innovation. In conclusion, the environmental economy is not only relevant as an academic concept, but also an important foundation in the formulation of sustainable development policies in Indonesia. This article is expected to enrich understanding and provide practical input for various parties in achieving a balance between the economy and ecology. aces obstacles in the form of weak law enforcement, low public awareness, and overlapping regulations